Investigation of the Effects of Nano-Particles in Targeted Radiation Therapy for Tumor Treatment - Hamza, Mohammed Adnan; Shahid, Amir Dhargham; Jadoua, Mustafa Abbas; Abdulkadhim, Bassem Jawad; al-kathem, Ola Hussein abd (American Journal of Botany and Bioengineering, 2025)
Nanoparticles have emerged as a promising tool to enhance the effectiveness of targeted radiation therapy for tumor treatment due to their unique physical, chemical, and biological properties. Despite significant advancements, challenges remain in optimizing nanoparticle-based radiosensitization and understanding their interactions with biological tissues. This study reviews the role of metal-based nanoparticles, particularly gold and silver nanoparticles, in improving the therapeutic ratio of radiotherapy by increasing localized radiation doses within tumor tissues. Through a combination of Monte Carlo simulations, experimental studies, and clinical insights, the findings demonstrate that nanoparticle-assisted radiotherapy significantly improves tumor control while minimizing damage to healthy tissues. Results confirm that nanoparticles not only enhance dose deposition via secondary electron production but also facilitate targeted drug delivery and photothermal effects. The study emphasizes that integrating nanoparticles into clinical radiotherapy could lead to improved treatment outcomes, reduced side effects, and the development of more effective cancer therapies. However, further research is needed to optimize dosimetry, biocompatibility, and clinical protocols for safe and effective implementation.